Influência do ambiente rural e urbano no desenvolvimento funcional de crianças de até seis anos de idade - Porfírio, Érica Gonçalvez; Navega, Flávia Roberta Faganello [UNESP] (My University, 2012)
The influence of the environment on psychomotor development of children is evidenced in many studies. Many factors can threaten children’s development and hinder the children with regard to functional activities. Objective: The objective of this research was to investigate the possible effects of urban and rural environment on the functional performance of children under six years old. Methods: The study included 30 children divided into two groups, one group consisted of 15 children of both genres with a mean age of 44.13 ± 20.97 months, residing in urban area and another for 15 children, both sexes with a mean age of 44.33 ± 20.91 months, residing in rural areas. All were tested using functional Pediatric Evaluation of Disability Inventory (PEDI), which is based on an evaluation trial, conducted through structured interviews with those responsible for the child. This test outlines the functional profi le of children in three performance areas: self-care, mobility and social function, evaluated in three parts (functional skills, caregiver assistance and modifi cations to the environment). In this study we used the parts I (funcional skills) and II (caregiver assistance) in three areas: self-care, mobility and social function. The collected data were analyzed by means of the Mann - Whitney test, with the level of signifi cance at p ≤ 0.05. Results: The results show no signifi cant difference in the areas of self-care and mobility, both in relation to functional abilities when the caregiver assistance. In the area of social function, there was a lower performance of children living in rural areas, in functional abilities (p = 0.027) and caregiver assistance (p = 0.028). Conclusion: Based on this information, we can conclude that children who live in rural areas have a worse development of the social functions of children living in urban areas.

Introdução: A interferência do ambiente no desenvolvimento psicomotor das crianças é evidenciada em muitos estudos. Muitos fatores podem ameaçar o desenvolvimento infantil e difi cultar as crianças no que diz respeito às atividades funcionais. Objetivo: O objetivo desta pesquisa foi investigar o possível efeito do ambiente urbano e rural no desempenho funcional de crianças de até seis anos de idade. Métodos: Participaram do estudo 30 crianças, divididas em dois grupos, sendo um grupo composto por 15 crianças, de ambos os generos, com média de idade de 44,13 ± 20,97 meses, que residem na área urbana e outro por 15 crianças, de ambos os sexos, com média de idade de 44,33 ± 20,91 meses, que residem na área rural. Todas foram avaliadas pelo teste funcional Pediatric Evaluation of Disability Inventory (PEDI), que é uma avaliação baseada em julgamento, realizada através de entrevista estruturada com os responsáveis pela criança. Este teste descreve o perfi l funcional de crianças em três áreas: habilidades funcionais (I), assistencia do cuidador (II) e modifi cações do ambiente (III). Sendo cada uma delas compostas por três partes: auto-cuidado, mobilidade e função social. Neste estudo foram utilizadas as partes I (habilidades funcionais) e II (assistência do cuidador), nas três áreas: auto-cuidado, mobilidade e função social. Os dados coletados foram analisados por meio do teste de teste de Mann – Whitney, estabelecendo-se o nível de signifi cância em p ≤ 0,05. Resultados: Os resultados mostram que não houve diferença signifi cativa nas áreas de auto-cuidado e mobilidade, tanto em relação às habilidades funcionais quando à assistência do cuidador. Já na área de função social, foi observado um desempenho inferior das crianças residentes na área rural, nas habilidades funcionais (p=0,027) e na assistência do cuidador (p=0,028). Conclusão: Com base nestas informações, podemos concluir que as crianças que vivem na área rural apresentaram um pior desenvolvimento das funções sociais do que as crianças que vivem na zona urbana.
Influence of rural and urban environment in functional development children under six years of age
Keywords: ambiente; desenvolvimento funcional; crianças; PEDI